Smart Antenna UKM Testbed for Digital Beamforming System. (12th February 2009) - Islam, Mohammad Tariqul; Misran, Norbahiah; Yatim, Baharudin
Abstract : A new design of smart antenna testbed developed at UKM for digital beamforming purpose is proposed. The smart antenna UKM testbed developed based on modular design employing two novel designs of L-probe fed inverted hybrid E-H (LIEH) array antenna and software reconfigurable digital beamforming system (DBS). The antenna is developed based on using the novel LIEH microstrip patch element design arranged into4 × 1 uniform linear array antenna. An interface board is designed to interface to the ADC board with the RF front-end receiver. The modular concept of the system provides the capability to test the antenna hardware, beamforming unit, and beamforming algorithm in an independent manner, thus allowing the smart antenna system to be developed and tested in parallel, hence reduces the design time. The DBS was developed using a high-performanceTMS320C6711 TM floating-point DSP board and a 4-channel RF front-end receiver developed in-house. An interface board is designed to interface to the ADC board with the RF front-end receiver. A four-element receiving array testbed at 1.88–2.22 GHz frequency is constructed, and digital beamforming on this testbed is successfully demonstrated.